AI-POWERED TOOLS FOR FASTER AND BETTER SOFTWARE DEVELOPMENT - Usama Nasir,; Hoor Fatima Yousaf,; Muhammad Abubakar Farooq,; Misbah Maqbool,; Haroon Ilyas,; Dilawar Khan Sukhera,; Rabia Abbas, (Spectrum of Engineering Sciences, 2025)
Artificial Intelligence (AI) has changed many fields, and making software is one of them. With more need for fast, good, and nice code, AI tools are being used a lot to help in different parts of building software, from making code and fixing it to finding mistakes and checking software. This paper looks at how AI tools affect the speed and quality of making software by conducting a test. We put AI tools into four main groups: code finishing, auto-checking, mistake finding, and project helping. A test was done with two groups of coders — one using old ways of working and the other using picked AI tools. Important measures, like code quality, time to make it, and mistake counts, were checked and compared. The results show that AI tools boost work speed and cut down on human mistakes, but problems like tool correctness and learning time are still there. These findings show AI can be a big deal in modern software building, giving useful ideas for coders and researchers.